2016
DOI: 10.1002/jcc.24684
|View full text |Cite
|
Sign up to set email alerts
|

Applying strong external electric field to thiophene‐based oligomers: A promising approach to upgrade semiconducting performance

Abstract: A key parameter dictating the rate of charge transfer (CT) is reorganization energy (λ), an energy associated with geometry changes during hole/electron transfer. We show that "ironing" the inter-ring dihedral angles of oligothiophenes via proper substitutions or insertions (e.g., -OR, -F or -C≡C-), decreases the λ and thus promotes CT according to Marcus equation. Our results demonstrate, to attain a smaller λ, extending oligomer length is only significant if the flattened backbone structure is realized. Of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…38 has a record-small λ (26 meV), which is nearly a quarter of the energy calculated for pentacene (96 meV) and b:2′,3′-f]thieno[3,2-b]thiophene (86 meV) and is also far smaller than those of the already synthesized compounds (27,28,29,31,32,35,36,39,40). 45−51 Compared to the dual substitution scheme, single-thiophene termination (29,33,37) is less effective in reducing λ at a similar molecule length. The benefit of designing dual thiophene-terminated benzothiophenes consistently holds for lateral expanded models (42,43,44,46,48 with λ in the range 46−126 meV), which are derivatized from 2D PAHs (9,10,11,12).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…38 has a record-small λ (26 meV), which is nearly a quarter of the energy calculated for pentacene (96 meV) and b:2′,3′-f]thieno[3,2-b]thiophene (86 meV) and is also far smaller than those of the already synthesized compounds (27,28,29,31,32,35,36,39,40). 45−51 Compared to the dual substitution scheme, single-thiophene termination (29,33,37) is less effective in reducing λ at a similar molecule length. The benefit of designing dual thiophene-terminated benzothiophenes consistently holds for lateral expanded models (42,43,44,46,48 with λ in the range 46−126 meV), which are derivatized from 2D PAHs (9,10,11,12).…”
mentioning
confidence: 93%
“…The conventional wisdom to construct organic molecules with small λ includes extending the π-conjugation length and employing a rigid molecular skeleton. ,, Inspiringly, Chao and co-workers , revealed with structurally rigid phenalenyl and phthalocyanine derivatives that by increasing the extent of local nonbonding character in frontier molecular orbitals, one can obtain extremely small λ (<100 meV). However, to apply this strategy in molecule design, visualization of the local patterns in frontier orbitals is necessary.…”
mentioning
confidence: 99%
“…21 Zhan et al conducted a detailed theoretical investigation on the effect of EEF on typical oligothiophenes to upgrade semiconducting performance with the help of EEF. 22 Stuyver et al reported that EEF induces shortening or lengthening of chemical bonds and can modulate chemical reactions and further reported that EEF is a potential commonly applicable "zapping" tool to facilitate elaborate chemical syntheses. 23 Moreover, several studies reported that molecules exhibit changes under the action of EEF, such as change in chemical bond, molecular charge distribution, energy, dipole moment, Raman, and infrared intensity.…”
Section: Introductionmentioning
confidence: 99%
“…González‐Henríquez et al explored the resonance effect on conductivity of polyesters containing thiophene and silarene after polarization under EEF and reported that the arrangement of dipoles increased electrical conductivity 21 . Zhan et al conducted a detailed theoretical investigation on the effect of EEF on typical oligothiophenes to upgrade semiconducting performance with the help of EEF 22 . Stuyver et al reported that EEF induces shortening or lengthening of chemical bonds and can modulate chemical reactions and further reported that EEF is a potential commonly applicable “zapping” tool to facilitate elaborate chemical syntheses 23 .…”
Section: Introductionmentioning
confidence: 99%
“…23 In addition to molecular packing, another environmental factor that is often overlooked is the external electric field (EEF). 24 In a typical field-effect transistor, the EEF can be generated by the electrodes, and the gate voltage controls the channel conductivity. To a reasonable approximation, the field strength (F) at the semiconductor−insulator interface is expressed as F = F i (k i / k s ), 25 where F i is the field strength felt in the insulator, and k i and k s are the dielectric constants respectively for the insulator and the semiconductor.…”
mentioning
confidence: 99%